Hubungan Excessive Daytime Sleepiness Terhadap Tingkat Konsentrasi Pada Mahasiswa Jurusan Keperawatan - Syafrinanda, Virginia; Yunani, Yunani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective: This study aims to determine the relationship between EDS and the concentration level of college students. Methods: This study used a cross-sectional design with a sample of 89 people. The EDS instrument was measured using the Epworth Sleepiness Scale and the concentration level instrument was the Stroop Test. Data analysis used the Chi-Square test. Results: The results showed that more than half of the college students experienced EDS (55.1%) compared to students who did not experience EDS (44.9%). Meanwhile, the concentration level of college students was in the poor category (40.4%), the less category (38.2%), and the moderate category (21.3%). The results of the statistical test showed a p-value of 0.021 (<0.05), meaning there is a significant relationship between EDS and concentration level. Conclusion: Based on the results of the research conducted, it appears that the analysis of the relationship between excessive daytime sleepiness and concentration levels in students indicates that students who experience excessive daytime sleepiness are more likely to experience it. Therefore, further research is needed to understand the factors that influence the occurrence of excessive daytime sleepiness and decreased concentration in students.